Risk Factors for Primary Clostridium difficile Infection; Results From the Observational Study of Risk Factors for Clostridium difficile Infection in Hospitalized Patients With Infective Diarrhea (ORCHID) - Davies, Kerrie; Lawrence, Jody; Berry, Claire; Davis, Georgina; Yu, Holly; Cai, Bing; Gonzalez, Elisa; Prantner, Ida; Kurcz, Andrea; Macovei, Ioana; Pituch, Hanna; Nováková, Elena; et al. (Frontiers in Public Health, 2020)
Background There are conflicting data on the risk factors for Clostridium difficile infection (CDI) in the literature. Aims To use two C. difficile infection (CDI) case-control study groups to compare risk factors in hospitalised patients with diarrhoea across different countries. Methods A multi-centre group of CDI cases/controls were identified by standardised testing from seven countries from the prior EUropean, multi-centre, prospective bi-annual point prevalence study of CLostridium difficile Infection in hospitalised patients with Diarrhoea (EUCLID). A second group of CDI cases/controls was identified from a single centre in Germany (parallel study site (PSS)). Data were extracted from the medical notes to assess CDI risk factors. Univariate analyses and multivariate logistic regression models were used to identify and compare risk factors between the two groups. Results There were 253 and 158 cases and 921 and 584 controls in the PSS and EUCLID groups, respectively. Significant variables from univariate analyses in both groups were age ≥65, number of antibiotics and prior hospital admission (all p<0.001). Congestive heart failure, diabetes, admission from assisted living or Emergency Department, proton pump inhibitors and chronic renal disease were significant in PSS (all p<0.05) but not EUCLID. Dementia and admitted with other bacterial diseases were significant in EUCLID (p<0.05) but not PSS. Following multivariate analyses, age ≥65, number of antibiotics and prior hospital admission were consistently identified as CDI risk factors in each individual group and combined datasets. Conclusion Our results show that the same CDI risk factors were identified across datasets. These were age ≥65 years, antibiotic use and prior hospital admission. Importantly, the odds of developing CDI increases with each extra antibiotic prescribed.